SPE Unconventional Resources Conference-Usa 2013
DOI: 10.2118/164537-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Vertical Multifractured Wells in Vaca Muerta Shale Oil Play, Argentina

Abstract: Oil production from the unconventional Vaca Muerta play is increasing as a result of a rigorous appraisal and exploitation strategy. Multiple wells have already demonstrated the potential of the Neuquén Basin, however optimization is still ongoing to determine the best practice for completing wells. A stand out difference of the Vaca Muerta play is its thickness (100 m to 450 m), as such a development strategy based solely on vertical wells is being considered in addition to the horizontal well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Additional information regarding this discussion can be found in the work done by Suarez et al (2013), Cipolla et al (2011) and Clarkson et al (2011).…”
Section: Geological Overviewmentioning
confidence: 99%
“…Additional information regarding this discussion can be found in the work done by Suarez et al (2013), Cipolla et al (2011) and Clarkson et al (2011).…”
Section: Geological Overviewmentioning
confidence: 99%
“…The technology of SRV is to achieve the important goal of increasing the contact area between matrix and fractures or fracture network as far as possible during the development of unconventional reservoirs [7,8]. The study and application of developing tight oil and shale oil reservoirs mostly focus on the natural depletion [9]. But some studies have shown that CO 2 flooding is an effective approach of enhanced oil recovery (EOR) in tight reservoirs [6,10,11].…”
Section: Introductionmentioning
confidence: 99%